Inhibitory control in the sober state as a function of alcohol sensitivity: a pilot functional magnetic resonance imaging (fMRI) study - Cofresí, Roberto U.; Upton, Spencer; Terry, Devon; Brown, Alexander A.; Piasecki, Thomas M.; Bartholow, Bruce D.; Froeliger, Brett (Frontiers in Human Neuroscience, 2025)
IntroductionLower sensitivity (LS) to acute alcohol promotes hazardous alcohol use, increasing risk for alcohol use disorder (AUD). Compared to peers with high sensitivity (HS), LS individuals exhibit amplified responses to alcohol cues and difficulty exerting inhibitory control (IC) over those cued responses. However, it is unclear whether LS and HS individuals differ in neural or behavioral responses when exerting IC over affectively neutral prepotent responses (i.e., domain-general IC). This fMRI pilot study examined domain-general IC and its neural correlates in young adult LS and HS individuals.MethodsParticipants (N = 32, Mage = 20.3) were recruited based on their Alcohol Sensitivity Questionnaire responses (HS: n = 16; LS: n = 16; 9 females/group) to complete an event-related fMRI IC task in a sober state. Retrospective assessments of alcohol craving, consumption, and problems were taken outside the lab.ResultsAlthough IC performance (accuracy) was numerically lower for the LS group (M[SD] = 0.527[0.125]) compared to the HS group (M[SD] = 0.595[0.124]), no significant difference was detected [t(30) = 1.55, p = 0.132]. Across groups, IC-related activity was observed in bilateral fronto-cortico-striatal circuitry, including dorsal striatum (DS) and dorsal/supragenual anterior cingulate cortex (dACC). Within group HS, IC-related dACC activity was greater among individuals reporting less intense (b-95 CI = [−0.201, −0.041], p = 0.004) and less frequent alcohol craving experiences (b-95 CI = [−0.131, 0.005], p = 0.068), whereas in group LS, IC-related dACC activity was greater among individuals reporting more intense (b-95 CI = [0.009, 0.140], p = 0.028) and more frequent alcohol craving experiences (b-95 CI = [0.022, 0.128], p = 0.007).DiscussionIn sum, while LS and HS individuals demonstrated similar domain-general IC performance and recruited similar neural resources to perform IC, findings suggest that compensatory over-activation of frontocortical nodes of the fronto-cortico-striatal IC circuitry may be related to affective-motivational aspects of AUD symptomatology (craving in daily life) among LS individuals. Based on these preliminary findings, future studies with larger samples are warranted to determine the extent to which domain-general IC performance associated with fronto-cortico-striatal IC circuit activation contributes to the alcohol use pathophysiology, and whether therapeutic interventions (e.g., non-invasive brain stimulation) targeting fronto-cortico-striatal IC circuitry may decrease AUD symptomatology.